(untitled) (Journal of Enam Medical College, 2012)
Background: Diabetic retinopathy is the commonest and usually the first observable vascular complication of diabetes mellitus. Along with hyperglycaemia, dyslipidaemia is a contributing factor for the occurrence of diabetic retinopathy. It is postulated that dyslipidaemia results in formation of hard exudate by increasing blood viscosity and altering the fibrinolytic system. A case control study was carried out in the department of Biochemistry, Bangabandhu Sheikh Mujib Medical University, Dhaka during the period of January 2006 to December 2007 to evaluate the serum lipid profile in newly diagnosed type 2 diabetic subjects with diabetic retinopathy. Materials and Methods: Total 85 newly diagnosed type 2 diabetic subjects were included in this study, 40 were cases having retinopathy and 45 were age and sex matched controls without retinopathy. Serum triglyceride (TG), total cholesterol (TC), low density lipoprotein cholesterol (LDL-C) and high density lipoprotein cholesterol (HDL-C) were compared between cases and controls. Unpaired t-test and chi-square test were done between groups as tests of significance. Results: All the parameters of lipid profile showed dyslipidaemic trend both in cases and controls. In the cases TG was significantly higher and HDL-C was significantly lower than that of controls (p < 0.05) whereas no significant difference was found between cases and controls with respect to serum TC and LDL-C. Conclusion: It can be concluded that high TG and low HDL-C are associated with diabetic retinopathy in newly diagnosed type 2 diabetes. DOI: http://dx.doi.org/10.3329/jemc.v1i2.11464 J Enam Med Col 2011; 1(2): 63-66